A LUTA POR RECONHECIMENTO, COMISSÃO NACIONAL DA VERDADE E MEMÓRIA COLETIVA - Araújo de Sousa, Vigevando (Cadernos do PET Filosofia, 2021)
The main objective of our research is to analyze the correlation between the struggle for recognition, the National Truth Commission – CNV (2012 - 2014) and collective memory. To achieve our goal, we propose to analyze memory from collective and social struggles evoking collective memory within an intersubjective relationship that involves disputes, negotiations, manipulations and forgetting. It is important to emphasize that the theoretical framework of our work is supported by the debate around the struggles for recognition. Therefore, we will verify, from Axel Honneth, the moral grammar of the struggles around this reciprocal recognition and how this dynamic happens in current social practices and, ipso facto, we intend to articulate the discussion of the communication paradigm with collective memory.